Understanding α-globin gene regulation and implications for the treatment of β-thalassemia - Mettananda, S; Gibbons, R; Higgs, D (Wiley, 2016)
Over the past three decades, a vast amount of new information has been uncovered describing how the globin genes are regulated. This knowledge has provided significant insights into the general understanding of the regulation of human genes. It is now known that molecular defects within and around the α- and β-globin genes, as well as in the distant regulatory elements, can cause thalassemia. Unbalanced production of globin chains owing to defective synthesis of one, and the continued unopposed synthesis of another, is the central causative factor in the cellular pathology and pathophysiology of thalassemia. A large body of clinical, genetic, and experimental evidence suggests that altering globin chain imbalance by reducing the production of α-globin synthesis ameliorates the disease severity in patients with β-thalassemia. With the development of new genetic-based therapeutic tools that have a potential to decrease the expression of a selected gene in a tissue-specific manner, the possibility of decreasing expression of the α-globin gene to improve the clinical severity of β-thalassemia could become a reality.